2016
DOI: 10.17795/zjrms-5984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ginger Hydroalcholic Extract on Rat Ileal Contraction in Vitro

Abstract: Background: Ginger is a medicinal plant with wide use around the world which has several therapeutic implications especially in gastrointestinal discomfort such as dyspepsia, flatulence, colic, diarrhea, nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Previous studies using isolated intestinal tract have reported that intrinsic pacemaker activity originates from ICCs of the Auerbach plexus, which are electrically coupled to smooth muscle cells [20,22]. ICCs play a major role in intestinal contraction without the involvement of motor neurons, hormones, or inflammatory mediators, and have been suggested to be modulated by several nutrients [23][24][25][26]. Another previous study reported an inhibitory action of caffeine on the smooth muscle contraction [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using isolated intestinal tract have reported that intrinsic pacemaker activity originates from ICCs of the Auerbach plexus, which are electrically coupled to smooth muscle cells [20,22]. ICCs play a major role in intestinal contraction without the involvement of motor neurons, hormones, or inflammatory mediators, and have been suggested to be modulated by several nutrients [23][24][25][26]. Another previous study reported an inhibitory action of caffeine on the smooth muscle contraction [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on herbal medicines, such as Lizhong Tang and Dangkwisoo-san, reported that these modify the gastrointestinal motility or pacemaker activities of ICCs [30,31]. In addition, some herbal extracts of the roots of ginger and Liriope Platyphylla Wang et Tang have been reported to mediate the contraction of the ileal smooth muscle in rats [32,33]. Reportedly, naringenin, a citrus peel component, inhibits the pacemaking activity in ICCs [34].…”
Section: Discussionmentioning
confidence: 99%
“…It can help to treat gastrointestinal diseases, including nausea and vomiting from motion sickness, diarrhea, loss of appetite, and dry mouth [8,9].…”
Section: Introductionmentioning
confidence: 99%